The uncertain future of a right school: a brief analysis of the proposals for environmental education in the Bosque school in the archipelago of Bailique, Amapá State, Brazil (Research, Society and Development, 2020)
In this new century, we seek to develop an education capable of awakening a conscious conduct towards environmental issues. Given this new educational scenario, this article aims to present a brief study on the importance of the relationships between education, environment and society, in the search for an affirmative relationship between man and nature, in order to achieve a new conception of education, focused on the sustainability theme. A bibliographic review was carried out taking into account the concepts of ecopedagogy, also known as Pedagogy of the Earth, which considers learning from the worldview and the model of education, and thus, like the pedagogical activities, developed at Escola Bosque do State of Amapá, located in the Bailique archipelago, in order to consider the particularities of the school and the community, valuing their cultural, historical, geographical and personal aspects, thus allowing the construction of a practical and broader reflection on the subject. The approach of this work aims to arouse the interest of future publications, regarding the importance of the Bosque do Amapá School although, today, the school no longer serves the community of Bailique, perishing attention in all aspects, from the structure to the administration to attend to the local society, as well as for the development of a highly sustainable environmental education, based on the foundations of ecopedagogy, which proposes the rescue of culture and popular wisdom, so that we can provide visibility and appreciation to the wealth of the archipelago's community. Bailique, where the school is located.